PENGEMBANGAN BAHAN AJAR DIGITAL BERBASIS KEARIFAN LOKAL MENGGUNAKAN GENIALLY PADA MATA PELAJARAN IPAS KELAS IV SD NEGERI 79 PALEMBANG - Kusuma, Muhammad Ilham; Nur Syafarudin; Sugiarti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop a local wisdom-based digital teaching material using Genially for IPAS (Natural and Social Sciences) subject in Grade IV of SD Negeri 79 Palembang. The research method used is Research and Development (R&D) with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The validity assessment was carried out by three validators consisting of lecturers and classroom teachers, obtaining an overall validity percentage of 90.6% with the category of "Very Valid". Practicality was measured through one-to-one trials (88.6%) and small group trials (90.8%), yielding an average of 89.7% with the category "Very Practical". Effectiveness was evaluated using the N-Gain score from pretest and posttest of 28 students, obtaining an average N-Gain score of 0.90 with the "High" category. The results show that the local wisdom-based digital teaching material using Genially is valid, practical, and effective for use in IPAS learning in Grade IV elementary school.